Mount Merapi in drawings and paintings; A dynamic reflection of nature, 1800-1930 - Mohammad, Ghamal Satya (Wacana, Journal of the Humanities of Indonesia, 2022)
Mount Merapi in Central Java is one of the world’s most studied volcanoes. The frequent eruptions of this volcano and the densely populated areas on its slopes make Merapi particularly important to scholars of the natural and social sciences. Considerable attention has been devoted to contemporary aspects of this volcano, including research into forecasting and monitoring possible volcanic activity and eruptions. However, research investigating artistic representations of Merapi in a historical context, particularly local artworks referring to how people responded to a natural hazard such as a volcanic eruption, is still rare. In this paper, I explore how artists in the period 1800-1930 have portrayed the volcanic activities in their drawings and paintings. Various historical data, including newspapers, reports, and records of volcanic eruptions, will be used to help interpret the accuracy of the paintings which depict Merapi at different moments in time. I argue that artists in the period under investigation were acutely aware of Merapi’s volcanic activities and depicted these in their drawings and paintings, because of the influence of science, which invokes interest in Merapi, landscape art, and a sense of humanitarianism. Their artworks are dynamic visual historical reflections of Merapi which testify to the power and beauty of nature.